Effectiveness of Drinking a Sweet-Tasting Snack Before Local Anesthetic Injection on Pain Perception among 5-Year-Old Children: A Split-Mouth Cross-Over Study - Hamidreza Poureslami; Jelveh Hashemi Nejad; Parnian Poureslami; Maryam Rad (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate the pain-relieving property of consuming sweet-tasting solution before dental injections. Material and Methods: In this single-blinded split-mouth study, fifty-two 5-year-old children who needed bilateral mandibular deciduous molars pulpotomies participated. The effect of drinking a cool liquid snack containing 10 milliliters of 12% sucrose solution (study group) or cool tap water (control group) with a straw before inferior alveolar nerve block injection was assessed regarding pain perception. The degree of discomfort was recorded after dental injections using the Wong-Baker Faces Pain Scale (WBFPS). Data were analyzed using SPSS version 26 and the Independent Sample Test. The statistical significance level was set at p<0.05. Results: Significantly lower WBFPS scores were reported for the test group (2.9231) compared to the study group (5.0000) (p<0.001). Conclusion: Drinking a cool sucrose solution with a straw before dental injections can aid in reducing the associated discomfort, resulting in better interaction with the child during dental sessions.